2020
DOI: 10.1111/jch.13825
|View full text |Cite
|
Sign up to set email alerts
|

Association of impaired arterial wall properties with the presence of coronary artery disease in patients with abdominal aortic aneurysms

Abstract: Pulse wave velocity (PWV) is a valid, clinically feasible marker of arterial stiffening, and a strong predictor of outcomes. The present study aimed to compare aortic elastic properties in patients with abdominal aortic aneurysms (AAA), with or without coronary artery disease (CAD), as well as healthy individuals. A total of 130 patients with AAA, eligible for interventional repair, and 30 healthy individuals, comprising the control group (HC), were enrolled. Presence of CAD was identified by coronary angiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…One metaanalysis included 5 eligible case-control studies enrolling a total of 2897 participants, and demonstrated a 2.5-fold prevalence of SRC in patients with AAA compared with subjects without AAA, suggesting that SRC may be associated with AAA. 4 Another meta-analysis, including 11 retrospective studies, demonstrated that the cumulative incidence of SRC among patients with AAA and no-AAA was 55% and 32%, respectively, with statistically higher odds of 3.02 of SRC among patients with AAA. 5 A common genetic or pathophysiologic link between aortic aneurysms and SRC has been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One metaanalysis included 5 eligible case-control studies enrolling a total of 2897 participants, and demonstrated a 2.5-fold prevalence of SRC in patients with AAA compared with subjects without AAA, suggesting that SRC may be associated with AAA. 4 Another meta-analysis, including 11 retrospective studies, demonstrated that the cumulative incidence of SRC among patients with AAA and no-AAA was 55% and 32%, respectively, with statistically higher odds of 3.02 of SRC among patients with AAA. 5 A common genetic or pathophysiologic link between aortic aneurysms and SRC has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Pulse wave velocity is higher in patients with AAA than healthy control patients, indicating that AAA may be associated with increased AS, in other words, reduced arterial elasticity; 3-5 aortic PWV was significantly higher in patients with AAA than control patients, after adjustment for age, sex, and mean arterial pressure. 4 Alterations in arterial wall composition, such as elastin and collagen, and inflammation were proposed as contributors to increased AS in AAA. In this study, the value of PWV was as high as 1919 ± 399 cm/s in all patients with AAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients present aortic vascular diseases and many cerebrovascular risk factors. A recent study showed an association of impaired arterial wall properties with the presence of coronary artery disease in patients with aortic aneurysms [7]. On the contrary, implantation of a relatively rigid tube in a previous healthy not atherosclerotic descending thoracic aorta may result in loss of compliance of the underlying aortic wall and cause impaired cardiac diastolic function and protracted systolic hypertension requiring antihypertensive treatment.…”
mentioning
confidence: 99%